PENINGKATAN PENGUNJUNG PADA HYPERMART MELALUI IKLAN DI HARIAN RAKYAT BENGKULU - Linda Irmawati; Marida Sariningsih; Syisva Nurwita (Professional: Jurnal Komunikasi dan Administrasi Publik, 2016)
Advertising has become a hope for the majority of companies that want their products embedded in the hearts of consumers. If an ad is not likely to have a major influence on the behavior of consumers, the advertising effectiveness is doubtful. The purpose of this study was to determine the increasing number of visitors at Hypermart Bengkulu through ads in Rakyat Bengkulu daily newspapers. This study used qualitative methods, that’s research that produces descriptive data in the form of words written or spoken of those that can be observed. Informants in this study were divided into two groups, namely the key informants consisting of 3 persons and key informants consisting of 4 people. The main theory used in this research was EPIC theory. The results in this study was, one element of the EPIC theory, namely is not going well because not every visitor read or subscribe to the Rakyat Bengkulu newspaper, so it effects on the increasing number in visitors at Hypermart Bengkulu.  Keywords: increasing, buyers, advertising, hypermart